2005
DOI: 10.1080/01140671.2005.9514365
|View full text |Cite
|
Sign up to set email alerts
|

Vineyard floor management improves wine quality in highly vigorousVitis vinifera’Cabernet Sauvignon’ in New Zealand

Abstract: Five inter-row soil management techniques were applied to a vigorous Vitis vinifera 'Cabernet Sauvignon' vineyard in Hawke's Bay, New Zealand-a permanent chicory (Chicorium intybus var. sativum 'Puna') cover crop; chicory sprayed with herbicide before veraison; incorporated pine (Pinus radiata) sawdust and bare soil maintained using cultivation or non-selective herbicide. Both chicory treatments significantly reduced the soil water content and shoot growth late in the season compared to the other treatments. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
49
3
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 16 publications
6
49
3
6
Order By: Relevance
“…For grapevines growing in water-limited areas, ground covers can be managed to compete with vines during the early vegetative growth, thus reducing their canopy leaf area and consequently reducing later transpiration losses (Dry and Loveys 1998;Monteiro and Lopes 2007). This management strategy also enhances grape and must quality (Ingels et al 2005;Pinamonti 1998;Wheeler et al 2005;Winkler et al 1974). However, it is important to impose these strategies in a timely fashion to avoid excessive water stress to the plants that could reduce fruit set or cause even premature defoliation.…”
Section: Cover Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…For grapevines growing in water-limited areas, ground covers can be managed to compete with vines during the early vegetative growth, thus reducing their canopy leaf area and consequently reducing later transpiration losses (Dry and Loveys 1998;Monteiro and Lopes 2007). This management strategy also enhances grape and must quality (Ingels et al 2005;Pinamonti 1998;Wheeler et al 2005;Winkler et al 1974). However, it is important to impose these strategies in a timely fashion to avoid excessive water stress to the plants that could reduce fruit set or cause even premature defoliation.…”
Section: Cover Cropsmentioning
confidence: 99%
“…Nevertheless, what it is commonly shown is that cover crop clearly interacts with the vines by improving soil properties, including spatial and temporal modifications of the water within the soil profile (Celette et al 2008). Furthermore, it has been shown that cover crop decreases vine vegetative vigor, as well as showing some increases in vine deeper root fraction, triggered by the competition with cover crop roots (Lopes et al 2011;Wheeler et al 2005). In a particular study, Pou et al (2011) considered not just what happens at soil level, but also, at plant level.…”
Section: Cover Cropsmentioning
confidence: 99%
“…Além disso, o excesso de vigor pode diminuir a atividade de enzimas que promovem a síntese desses compostos e causar queda de qualidade enológica da uva e do vinho (Keller & Hrazdina, 1998;Chavarria et al, 2011). O vigor adequado da parte aérea das videiras proporciona rendimento e composição da uva e de seu mosto mais propícios à vinificação (Wheeler et al, 2005), o que possibilita a elaboração de vinhos tintos com maior teor de compostos fenólicos totais e antocianinas (Xi et al, 2010), favoráveis a características como cor, corpo e adstringência do vinho (Xi et al, 2011).…”
Section: Introductionunclassified
“…Entretanto, estas plantas também podem ser usadas para diminuir a disponibilidade de água e nutrientes no solo, especialmente do N, com o intuito de diminuir o vigor vegetativo das videiras (Dry & Loveys, 1998;Wheeler et al, 2005;Lopes et al, 2008). Além disso, a roçagem da parte aérea das plantas de cobertura, nas linhas de cultivo, com subsequente transferência dos resíduos culturais para as entrelinhas, pode diminuir a disponibilidade de nutrientes na faixa de plantio -onde normalmente se encontra a maior densidade de raízes (Eissenstat, 2007) -, o que pode contribuir para o menor desenvolvimento vegetativo das plantas.…”
Section: Introductionunclassified
“…These aspects are important to vine growth, and therefore vineyard floor management has implications for wine quality (Nauleau 1997, Afonso et al 2003, Wheeler et al 2005, Nazrala 2008). The best practice for each vineyard site is determined in part by vine age, vineyard design, soil type, and climatic conditions of the vineyard site (Ripoche et al 2010, Sweet andSchreiner 2010).…”
mentioning
confidence: 99%